Neosomes of tungid fleas on wild and domestic animals - Linardi, Pedro Marcos (Springer Berlin Heidelberg, 2014)
Tunga is the most specialized genus among the Siphonaptera because adult females penetrate into the skin of their hosts and, after mating and fertilization, undergo hypertrophy, forming an enlarged structure known as the neosome. In humans and other warm-blooded animals, neosomes cause tungiasis, which arises due to the action of opportunistic agents. Although its effects on humans and domestic animals are well described in the literature, little is known about the impact of tungiasis on wild animals. This review focuses on the morphology, taxonomy, geographical distribution, hosts, prevalence, sites of attachment, and impact of tungid neosomes on wild and domestic animals. Because neosomes are the most characteristic form of the genus Tunga and also the form most frequently found in hosts, they are here differentiated and illustrated to aid in the identification of the 13 currently known species. Perspectives for future studies regarding the possibility of discovering other sand flea species, adaptation to new hosts, and the transfer of tungids between hosts in natural and modified habitats are also presented. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00436-014-4081-8) contains supplementary material, which is available to authorized users.